Determining the Opinions of Parents with Children with Special Needs on Digital Games - DENİZ, RABİA; KILIÇ, FİDAN GÜNEŞ GÜRGÖR (İstanbul Kültür Üniversitesi, 2024)
With the development of technology, interest in digital games has increased in children with typical development and children with special needs. Many digital games with different contents are played by children with special needs. The research was carried out with the parents of diagnosed children aged 6-13 years. The aim of the research is to determine the views of parents of children with special needs on digital games. The research was designed with phenomenology (phenomenology), one of the qualitative research methods, and the data were created and analyzed using content analysis. A semi-structured interview form and a questionnaire containing demographic information were used in the research. As a result of the data, codes were created and thanks to them, themes and sub-themes were reached. In the research, digital game theme and sub-themes were reached. In consequence of them, it was obtained that children with special needs mostly prefer war games, their purpose of playing games is entertainment, they mostly prefer mobile phones while playing games, and they play games for at least two hours a day. In addition to the findings that digital games contribute positively to the educational processes, skills and development of children with special needs, there were also findings that digital games have negative effects such as children not being able to spare time for their lessons and spending all their time in digital games.
Özel Gereksinimli Çocuğu olan Ailelerin Dijital Oyunlara Yönelik Görüşlerinin Belirlenmesi
Keywords: Children with Special Needs; Game; Digital Game; Parents; Phenomenology; Technology